2020
DOI: 10.3389/fpsyt.2020.567189
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary Autobiographical Memories in Schizophrenia: Characteristics and Conditions of Elicitation

Abstract: Involuntary autobiographical memories are mental representations of personally experienced past events that come to mind spontaneously, with no preceding attempt to recall them. They have been showed to be more frequent and more emotional in the psychosis continuum. Although schizophrenia is strongly associated with thought disorders, including cognitive intrusions of thought, images, semantic knowledge, research on patients' involuntary autobiographical memories is limited. We undertook two studies to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Overall, patients tend to lack a sense of agency which leads them to attribute their thoughts to someone else and be confident in this misattribution (Swiney & Sousa, 2013). In the case of autobiographical memory, Allé et al (2020) showed that patients have little trust in their involuntary memories. They interpreted this result as a consequence of a lack of control during retrieval and difficulties in seeing such memories as self‐generated; thus having deficits in metacognitive processes.…”
Section: Retrieval Process In Autobiographical Memorymentioning
confidence: 99%
“…Overall, patients tend to lack a sense of agency which leads them to attribute their thoughts to someone else and be confident in this misattribution (Swiney & Sousa, 2013). In the case of autobiographical memory, Allé et al (2020) showed that patients have little trust in their involuntary memories. They interpreted this result as a consequence of a lack of control during retrieval and difficulties in seeing such memories as self‐generated; thus having deficits in metacognitive processes.…”
Section: Retrieval Process In Autobiographical Memorymentioning
confidence: 99%
“…Relatively few studies have investigated 'involuntary MTT,' for which past or future events are spontaneously generated when participants are engaged with other tasks. For instance, two recent studies investigated involuntary MTT in patients with schizophrenia (Allé et al, 2020(Allé et al, , 2021. Therefore, future research should compare voluntary and involuntary MTT in psychiatric patients, and conduct cross-diagnosis comparisons of MTT.…”
Section: Mtt Impairments In Psychiatric Patients At the Behavioral Levelmentioning
confidence: 99%
“…Of these additional questions, only the spontaneous rehearsal and memory coherence are relevant for the present article (see Table 2). The analysis of other qualitative characteristics is reported elsewhere (Allé et al, 2020).…”
Section: Memory Diarymentioning
confidence: 99%